Learning to Salsa new steps in U.S.-Cuba relations - Huddleston, Vicki; Pascual, Carlos (Brookings Institution Press, 2010)
"Drawing on simulation exercises involving role playing and extensive debates, explores how major developments within or outside Cuba might open opportunities for the U.S. to reengage with the island nation and support Cuban actors in initiating change from within, and reveals specific challenges to crafting a new U.S. approach"--Provided by publisher.
Keywords: Außenpolitik; Politik; Engagement (Philosophy) -- Political aspects; Political games; Role playing -- Political aspects; Social change -- Cuba; USA; Cuba -- Foreign relations -- United States; Cuba -- Politics and government -- 1990-; Cuba -- Relations -- United States; Cuba -- Social conditions -- 1959-; United States -- Foreign relations -- Cuba; United States -- Relations -- Cuba; Kuba